Ψ-Xenin-6 enhances sitagliptin effectiveness, but does not improve glucose tolerance. Issue 2 (May 2020) - Craig, Sarah L; Gault, Victor A; Hamscher, Gerd; Irwin, Nigel
Abstract : Recent studies have characterised the biological properties and glucose-dependent insulinotropic polypeptide (GIP) potentiating actions of an enzymatically stable, C-terminal hexapeptide fragment of the gut hormone xenin, namely Ψ-xenin-6. Given the primary therapeutic target of clinically approved dipeptidyl peptidase-4 (DPP-4) inhibitor drugs is augmentation of the incretin effect, the present study has assessed the capacity of Ψ-xenin-6 to enhance the antidiabetic efficacy of sitagliptin in high fat fed (HFF) mice. Individual administration of either sitagliptin or Ψ-xenin-6 alone for 18 days resulted in numerous metabolic benefits and positive effects on pancreatic islet architecture. As expected, sitagliptin therapy was associated with elevated circulating GIP and GLP-1 levels, with concurrent Ψ-xenin-6 not elevating these hormones or enhancing DPP-4 inhibitory activity of the drug. However, combined sitagliptin and Ψ-xenin-6 therapy in HFF mice was associated with further notable benefits, beyond that observed with either treatment alone. This included body weight change similar to lean controls, more pronounced and rapid benefits on circulating glucose and insulin as well as additional improvements in attenuating gluconeogenesis. Favourable effects on pancreatic islet architecture and peripheral insulin sensitivity were more apparent with combined therapy. Expression of hepatic genes involved in gluconeogenesis and insulin action were partially, or fully, restored to normal levels by the treatment regimens, with beneficial effects more prominent in the combination treatment group. These data demonstrate that combined treatment with Ψ-xenin-6 and sitagliptin did not alter glucose tolerance but does offer some metabolic advantages, which merit further consideration as a therapeutic option for type 2 diabetes.